Safety and Clinical Outcomes of Low-Intensity Versus Standard Monitoring Following Thrombolysis in Acute Ischemic Stroke: A Systematic Review - Syed Akbar Imam, Rutbaa Ayaz Shaikh, Bilal Khan (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Intravenous thrombolysis is the cornerstone of acute ischemic stroke (AIS) treatment, but standard post-thrombolysis monitoring is resource-intensive and difficult to implement in low- and middle-income countries (LMICs) with limited ICU access. Low-intensity monitoring (LIM) protocols have been proposed as alternatives, but evidence on their safety and clinical outcomes remains limited and fragmented. Objective: This systematic review evaluates whether LIM offers a viable, resource-efficient alternative to conventional monitoring in thrombolysed AIS patients. Methods: Following PRISMA 2020 guidelines, a systematic search was conducted in June 2025 across PubMed, Google Scholar, Cochrane Library, and ClinicalTrials.gov for studies involving adult AIS patients treated with IV thrombolysis. Search terms included combinations of “low-intensity monitoring,” “standard monitoring,” and “acute ischemic stroke.” Eligible studies compared LIM and standard protocols and reported outcomes like 90-day modified Rankin Scale (mRS), symptomatic intracerebral hemorrhage (sICH), NIHSS, ICU admission, or hospital stay. Case reports, editorials, animal studies, and non-comparative designs (except single-arm safety trials used for contextualizing safety) were excluded. After screening, three studies were included: one cluster RCT, one retrospective cohort, and one single-arm safety trial. Three reviewers independently extracted data. Risk of bias was assessed using Cochrane RoB 2.0 and the Newcastle-Ottawa Scale. Due to design and outcome heterogeneity, a meta-analysis was inappropriate; instead, a narrative synthesis was performed Results: Across the three studies, 5,161 patients were analyzed. The OPTIMISTmain RCT reported similar 90-day functional independence (mRS 0–2) in LIM (31.7%) and standard care (30.9%) groups (RR 1.03; 95% CI, 0.92–1.15; p=0.61). sICH was rare in OPTIMISTmain (0.2–0.4%) but higher in the cohort study (4.9%). ICU admissions were comparable, though early escalation occurred more in the cohort. The safety trial reported favorable outcomes without critical events. Nurses in OPTIMISTmain found LIM acceptable due to reduced burden. Conclusion: LIM appears feasible in resource-constrained settings. However, limited studies restrict generalizability. Patient selection, staff training, and structured protocols are essential. Further large-scale studies are needed to validate implementation and risk stratification tools. Keywords: Stroke, Thrombolytic Therapy, Developing Countries